The natural course of IgG4-related ophthalmic disease after debulking surgery: a single-centre retrospective study. Issue 1 (9th August 2019) - Ominato, Jun; Oyama, Tokuhide; Cho, Hiroyuki; Shiozaki, Naoya; Umezu, Hajime; Takizawa, Jun; Fukuchi, Takeo
Abstract : Objective: This study aimed to examine the natural course and relapse rate of IgG4-related ophthalmic disease (IgG4-ROD) after debulking surgery in Japanese patients. Methods and analysis: This retrospective review included patients with IgG4-ROD who did not undergo further treatment following debulking surgery. The patients were diagnosed between January 2009 and December 2018 at the Department of Ophthalmology and Pathology, Niigata University Medical and Dental Hospital. The main outcome measures included postoperative IgG4-ROD recurrence rate and differences between patients with and without recurrent disease. Results: Fifteen patients (six male, 9 female; 61.8±16.2 years) were included. Twelve patients (80.0%) had dacryoadenitis disease and three patients (20.0%) had orbital fat tissue disease. About 70%–100% of the lesion was resected in the debulking surgery and the pathological diagnosis was rendered. A definitive diagnosis was made in 13 cases (86.7%) and a probable diagnosis in 2 cases (13.3%). Patients were followed up for 39.0±25.5 months following operation. All patients had lesion volume reduction and patients with dacryoadenitis had eyelid swelling improvement after surgery. Two patients (13.3%) had disease recurrence and six patients (40.0%) had extraophthalmic lesions. There was no statistically significant difference in clinical features between relapsed and non-recurring cases. Conclusion: We observed a 13.3% relapse rate following debulking surgery in patients with IgG4-ROD who did not undergo further treatment. This rate is lower than the documented relapse rate of 30%–70% following oral prednisolone therapy. Therefore, debulking surgery may be a treatment option for IgG4-ROD.